2021
DOI: 10.1038/s42003-020-01533-9
|View full text |Cite
|
Sign up to set email alerts
|

Late Campanian fossil of a legume fruit supports Mexico as a center of Fabaceae radiation

Abstract: Fabaceae is one of the most diverse angiosperm families and is distributed across the globe in a variety of environments. The earliest evidence of the family, previous to this work, was from Paleogene sediments where it was found to be diverse in many fossil assemblages around the world. Here, we describe a fossil legume fruit from the Olmos Formation (upper Campanian) in northern Mexico. We designated the fossil fruit as Leguminocarpum olmensis Centeno-González, Martínez-Cabrera, Porras-Múzquiz et Estrada-Rui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…While the number of fossils collected influences these data, they nonetheless indicate floral turnover at the Pu2/Pu3 boundary. Importantly, we see the first appearace of the angiosperm family Leguminosae (= Fabaceae) outside of Central America (Centeno-Gonzalez et al 2021 ) anywhere in the world in the form of both fossil legume pods and leaflets at this stratigraphic level (Lyson et al 2019a ). Legumes would have represented a new, high-protein food source for herbivores such as T. taoensis on the early Paleocene landscape.…”
Section: Geological Setting Age Control and Paleobotanical Contextmentioning
confidence: 83%
“…While the number of fossils collected influences these data, they nonetheless indicate floral turnover at the Pu2/Pu3 boundary. Importantly, we see the first appearace of the angiosperm family Leguminosae (= Fabaceae) outside of Central America (Centeno-Gonzalez et al 2021 ) anywhere in the world in the form of both fossil legume pods and leaflets at this stratigraphic level (Lyson et al 2019a ). Legumes would have represented a new, high-protein food source for herbivores such as T. taoensis on the early Paleocene landscape.…”
Section: Geological Setting Age Control and Paleobotanical Contextmentioning
confidence: 83%
“…60–58 Ma (Herrera et al, 2019 ; Carvalho et al, 2021 ). Centeno‐González et al ( 2021 ) reported a legume‐like fossil fruit from the Campanian (Late Cretaceous) Olmos Formation in northern Mexico. However, in our opinion, the resemblance of the single fossil fruit to the legume family is only superficial; structural details are not sufficient to be confident of the assignment to the Leguminosae.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, physical dormancy or DT is explained through an LEA gene regulatory network, which is now known to have evolved through WGD (Verdier et al, 2013;Marques, 2018;Artur et al, 2019a). Although older, Fabaceae-like fruits are reported from the late Campanian in Mexico (Centeno-González et al, 2021), these fruits lack diagnostic characteristics associated with this family (Herendeen , 2022). The oldest confirmed Fabaceae fruits first appear in seasonal tropical forests in the Denver Basin, Colorado, slightly above the KPB (Lyson et al, 2019;Herendeen et al, 2022).…”
Section: Discussionmentioning
confidence: 99%